The unseen struggle: Intersectionality and healthcare access for women in Nigeria's low-income communities - Ibitoye, Anthonia Folasade (Center for Sociological Studies and Community Developmen, 2025)
One of the major challenges for women in low-income Nigerian communities is limited access to healthcare, leading to poor health outcomes and higher mortality rates. This study examines the barriers faced by women in Ekiti State using intersectional feminist theory and a cross-sectional design. Data were collected through structured questionnaires from 300 women aged 18 and above, selected via multistage sampling (stratified, purposive, and simple random). Analysis was conducted with SPSS version 25.0 using descriptive (frequency and percentages) and inferential (multiple regression) statistics. Findings show that all respondents experienced difficulties in accessing healthcare: 86% reported financial constraints, 84.7% cited lack of affordable and quality facilities, and 80% identified distance as a major barrier. Marital status (β = 0.373, p 0.05), occupation (β = 0.243, p 0.05), age (β = 0.080, p 0.05), and education (β = 0.051, p 0.05) were significant predictors of healthcare access challenges. The study concludes that tailored interventions are essential to address these barriers. To improve access and reduce mortality, it recommends increased healthcare funding, financial protection mechanisms, expanded health education, stronger social support networks, and contextspecific interventions.